Spectrum of modern geography : essays in memory of Prof. Mohammad Anas - Anas, Mohammad, 1925-; Shafi, Mohammad, 1924-; Raza, Mehdi, 1931- (New Delhi : Concept Pub. Co., 1986)
Festschrift honoring Mohammad Anas, 1925-1983, professor of geography, Aligarh Muslim University; comprises articles mostly in Indian context.
Includes bibliographies and index.
Keywords: Anas, Mohammad, -- 1925-; Geography